Pemanfaatan media dedak padi yang difermentasi dan tidak difermentasi untuk perbanyakan Alona sp. - Sanggaria, Ayu W.; Solang, Jhonly; Pangkey, Henneke; Kreckhoff, Reni L.; Sambali, Haryani; Watung, Juliaan Ch.; Kambey, Alex D. (Universitas Sam Ratulangi, 2022)
This study aimed to analyze the use of fermented rice bran media for the propagation of Alona sp. The method used is an experimental method, using one-way ANOVA, with three treatments, namely fermented rice bran media, unfermented rice bran media, and water. Each treatment was repeated 3 times, so that 9 experimental units were obtained. The observed variable was the density of Alona sp. The results showed that the density of Alona sp. that were cultured on fermented rice bran media was significantly different from that of unfermented rice bran and water.